Electrode and electrochemical device including same

JP2025504922AActive Publication Date: 2025-02-19LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024544502
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-14
Filing Date
2023-01-30
Publication Date
2025-02-19
Estimated Expiration
2043-01-30

AI Technical Summary

Benefits of technology

【0024】 本発明による電極は、複数の単位電極活物質層が積層されて形成された多層構造の電極に関する。前記電極は、各単位電極活物質層が電極材料を含むグラニュールが集積されて形成されたものであって、各単位層に使用される電極活物質が異なっても単位層の界面付近で電極活物質の混入が発生しないため、異種の電極活物質間の電気化学的特性の干渉が少ない。また、前記電極活物質層は、集電体側により近く配置された単位層よりも電極の表面側により近く配置された単位層の気孔度が高い。これによって、電極の電解液の濡れ性及びイオン伝導度が改善される。また、本発明による電極は、各単位電極活物質層の形成のためのカレンダリング工程時に圧力調節が不要であり、同じ圧力を維持しても各層に含まれる材料の性質によって電極が各単位電極活物質層毎に気孔度の勾配を有することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504922000001_ABST
    Figure 2025504922000001_ABST
Patent Text Reader

Abstract

The electrode according to the present invention relates to an electrode having a multi-layer structure formed by stacking a plurality of unit electrode active material layers. In the electrode, each unit electrode active material layer is formed by accumulating granules containing an electrode material, and even if different electrode active materials are used in each unit electrode active material layer, there is no mixing of the electrode active materials near the interface of the unit electrode active material layers, so that there is little interference in electrochemical properties between different types of electrode active materials. In addition, the electrode active material layer has higher porosity in the unit electrode active material layers disposed closer to the electrode surface than in the unit layers disposed closer to the current collector. This improves the wettability of the electrode to the electrolyte and ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode manufactured by a dry method in which a plurality of granules containing an electrode active material and an electrode binder are compressed, and an electrochemical device including the electrode.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0013757 filed on January 28, 2022 and Korean Patent Application No. 10-2022-0031451 filed on March 14, 2022, and the entire contents disclosed in the specification and drawings of said application are incorporated herein by reference. [Background technology]

[0003] As the use of fossil fuels increases rapidly, the demand for alternative and clean energy is increasing, and one of the most active research fields is the field of power generation and storage using electrochemistry. Currently, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and its range of use is expanding. Lithium secondary batteries, which are representative of such secondary batteries, are not only used as an energy source for mobile devices, but are also being used as a power source for electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution, and their range of use is expanding as an auxiliary power source for grid-based power generation.

[0004] Recently, various researches have been conducted on the development of batteries that use multiple electrode active materials to improve battery performance. When multiple electrode active materials are mixed to form a single electrode active material layer, the battery performance is deteriorated due to interference between the active materials. Therefore, a method has been considered to improve electrode characteristics and battery performance by forming multiple electrode active material layers and specializing the function of each layer during battery manufacturing.

[0005] However, the conventional electrode manufacturing method using a coating method of a slurry for forming an electrode active material layer has a problem that it is difficult to achieve the purpose of improving the effect of manufacturing a multi-layer electrode. In the manufacturing process of a multi-layer electrode using a slurry coating method, a wet-on-wet method is mainly used in which an upper slurry is applied to the surface of a lower slurry before the lower slurry is dried, and since the slurry exhibits fluidity, the upper and lower slurries are mixed at the interlayer interface, making it difficult to completely block the interference between the active materials. Meanwhile, after the electrode slurry is dried, a pressurizing process is performed to match the previously designed target dimensions such as the thickness and porosity of the electrode. When an electrode is manufactured using the wet-on-wet coating method of the slurry, the pressurizing process is performed in a manner in which pressure is applied through the surface of the electrode, and in this case, pressure is concentrated near the surface of the electrode compared to other parts, and the porosity near the surface of the electrode may be excessively reduced. If the porosity of the surface of the electrode is reduced in this way, the wettability of the electrolyte and ionic conductivity may be reduced.

[0006] In order to solve the above problems, there is a demand for a multilayer electrode in which unit electrode active material layers are stacked, in which there is little mixing of the upper and lower electrode active materials at the interlayer interface, and in which the porosity of the upper part of the electrode is appropriately maintained in order to improve the inflow of the electrolyte and ionic conductivity. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a multilayer electrode for an electrochemical device in which the interlayer electrode active material is less mixed in.

[0008] Another object of the present invention is to provide a multi-layer electrode having a high porosity in the upper part of the electrode.

[0009] It is yet another object of the present invention to provide a dry electrode including granular particles as a multi-layer electrode having little interlayer electrode active material contamination and high porosity in the upper part of the electrode.

[0010] The objects and advantages of the present invention can be realized by the means and combinations thereof recited in the claims. [Means for solving the problem]

[0011] According to a first aspect of the present invention, there is provided an electrode for an electrochemical device, comprising a current collector and an electrode active material layer disposed on at least one surface of the current collector, The electrode active material layer includes a unit electrode active material layer in which a plurality of granules including an electrode active material and an electrode binder are accumulated by compression bonding, and a first unit electrode active material layer to an n-th unit electrode active material layer are sequentially laminated on a surface of the current collector, where n is an integer of 2 or more, Among the unit electrode active material layers included in the electrode active material layer, the nth unit electrode active material layer disposed at the top has the highest porosity.

[0012] According to a second aspect of the present invention, in the first aspect, the n is 3 or more and 10 or less.

[0013] According to a third aspect of the present invention, in the first or second aspect, the porosity of the n-th unit electrode active material layer which is the uppermost layer of the electrode active material layers is 40 vol % or less.

[0014] According to a fourth aspect of the present invention, in any one of the first to third aspects, the first unit electrode active material layer has a porosity of 20 vol % or more.

[0015] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, each unit electrode active material layer has a porosity that increases with increasing distance from the surface of the current collector.

[0016] According to a sixth aspect of the present invention, in the first to fifth aspects, each unit electrode active material layer contains a plurality of types of electrode active materials, and the combination of components (types) of the plurality of electrode active materials in each unit electrode active material layer is the same, but the content ratio between each component in each unit electrode active material layer is different.

[0017] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the granules contained in each unit electrode active material layer contain multiple types of electrode active materials, and the combination of components (types) of the multiple electrode active materials in the granules of each unit electrode active material layer is the same, but the content ratio of the components in each granule in each unit electrode active material layer is different.

[0018] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, in each unit electrode active material layer, the difference between the binder content (wt%) in the upper 100 wt% and the binder content (wt%) in the lower 100 wt% is 10 wt% or less at the upper and lower parts based on ½ of the height of the unit electrode active material layer.

[0019] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, n is 3 or more, and the difference in porosity between the lowermost first unit electrode active material layer and the uppermost nth unit electrode active material layer is 5 vol% to 20 vol%.

[0020] According to a tenth aspect of the present invention, in any one of the first to ninth aspects, the electrode is a negative electrode, and the electrode active material includes at least one selected from the group consisting of natural graphite, artificial graphite, and lithium (Li), silicon (Si), tin (Sn), a lithium alloy, a silicon alloy, a tin alloy, a silicon oxide, a tin oxide, a lithium-containing compound, a silicon-containing compound, and a tin-containing compound.

[0021] According to an eleventh aspect of the present invention, in any one of the first to tenth aspects, the granules include an electrode conductive material.

[0022] According to a twelfth aspect of the present invention, in any one of the first to eleventh aspects, a primer layer is formed on at least one side of the current collector, covering all or at least a part of the surface, and the primer layer includes a conductive material and a binder.

[0023] According to a thirteenth aspect of the present invention, there is provided a method for manufacturing an electrode according to any one of the first to twelfth aspects, the method comprising the steps of applying an electrode powder to one surface of a current collector and pressing the powder to form a first unit electrode active material layer having a layered structure having a predetermined thickness, and then repeating the steps of applying an additional electrode powder to a surface of each unit electrode active material layer formed in the previous step and pressing the powder to form a unit electrode active material layer (n-1 times) to manufacture an electrode including n unit electrode active material layers, the electrode having a structure according to the first aspect, and n being an integer of 2 or more. Effect of the Invention

[0024] The electrode according to the present invention relates to an electrode having a multi-layer structure formed by stacking a plurality of unit electrode active material layers. In the electrode, each unit electrode active material layer is formed by accumulating granules containing an electrode material, and even if different electrode active materials are used in each unit layer, there is no mixing of the electrode active materials near the interface of the unit layers, so that there is little interference in electrochemical properties between different types of electrode active materials. In addition, the electrode active material layer has a higher porosity in the unit layer disposed closer to the surface side of the electrode than in the unit layer disposed closer to the current collector side. This improves the wettability of the electrolyte and ionic conductivity of the electrode. In addition, the electrode according to the present invention does not require pressure adjustment during a calendaring process for forming each unit electrode active material layer, and the electrode may have a porosity gradient for each unit electrode active material layer depending on the properties of the material contained in each layer even when the same pressure is maintained.

[0025] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited to only the matters described in the drawings. [Brief description of the drawings]

[0026] [Figure 1] 1 is a schematic cross-sectional view of an electrode according to an embodiment of the present invention; [Diagram 2]1 is a Nyquist plot of the batteries of each of the examples and comparative examples. [Diagram 3] FIG. 1 is a schematic diagram showing a surface portion and a center portion of a granule 100 according to one embodiment of the present invention. [Figure 4] 1 is a SEM image of the first granules obtained by the above production. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The present invention will be described in detail below. However, the present invention is not limited to the following content, and each component may be modified in various ways or mixed selectively as necessary. Therefore, it should be understood that all modifications, equivalents, or alternatives falling within the spirit and technical scope of the present invention are incorporated.

[0028] Throughout the specification, when a part "comprises" a certain element, it does not mean excluding other elements, but means that the part may further include other elements, unless otherwise specified.

[0029] The terms "about," "substantially," and the like, used throughout this specification, when given the meaning inherent in the manufacturing and material tolerances, are used to mean a numerical value or a approximation thereof, and are used to prevent unconscionable infringers from unfairly using disclosures in which precise or absolute numerical values ​​are recited to aid in the understanding of this application.

[0030] Throughout this specification, the phrase "A and / or B" means "A or B, or all of these."

[0031] Certain terminology used herein is for convenience and is not limiting. Terms such as "top," "bottom," "left," "right," "front," "rear," "inside," and "outside" are used to describe relative positions and orientations of components relative to one another, rather than absolute positions, or may indicate positions and orientations in the drawings to which reference is made. The above terms include other words containing these, derivatives thereof, and words of similar meaning.

[0032] As used herein, the "glass transition temperature, Tg," may be measured by conventional methods known in the art, for example, by differential scanning calorimetry (DSC).

[0033] In the present specification, the term "porosity" refers to the ratio of the volume of pores to the total volume of a structure, and is expressed in units of %, and may be used interchangeably with terms such as porosity and porosity. In the present invention, the measurement of the porosity is not particularly limited, and in one example of the present invention, for example, the porosity can be measured by BET (Brunauer-Emmett-Teller) measurement method using nitrogen gas or mercury penetration method (Hg porosimeter) and ASTM D-2873. Alternatively, the true density of the measurement object can be calculated from the density (apparent density) of the measurement object, the composition ratio of the materials contained in the measurement object, and the density of each component, and the porosity can be calculated from the difference between the apparent density and the true density (net density).

[0034] The term "average particle size D50" used in the specification means the particle size at 50% of the cumulative particle number distribution by particle size, and the particle size may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the diffraction pattern difference according to particle size when the particles pass through a laser beam. The D50 particle size can be measured by calculating the particle diameter at the 50% point of the cumulative particle number distribution by particle size in the measuring device.

[0035] In this specification, the "thickness" of each layer included in the electrode may refer to a value measured by a known method for measuring thickness. The method for measuring thickness is not limited thereto, but may be, for example, a value measured using a thickness meter (Mitutoyo, VL-50S-B).

[0036] The "specific surface area" used in the present specification may be a value measured by a known method for measuring a specific surface area. The method for measuring the specific surface area is not limited thereto, and may be, for example, a value measured by a flow method or a stationary method.

[0037] The present invention relates to an electrode for an electrochemical device. The electrode may be a positive electrode or a negative electrode depending on the polarity of the electrode. The electrochemical device of the present invention includes all devices that perform electrochemical reactions, specifically, for example, all kinds of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors such as supercapacitor devices. In the present invention, the electrochemical device is preferably a secondary battery, more preferably a lithium ion secondary battery. In a specific embodiment of the present invention, the electrochemical device may include a positive electrode or a negative electrode, or both, according to the present invention.

[0038] An electrode according to one aspect of the present invention includes a current collector and an electrode active material layer disposed on at least one surface of the current collector.

[0039] The electrode active material layer is formed by introducing granules including an electrode active material and an electrode binder. In a specific embodiment of the present invention, the electrode active material layer includes two or more unit electrode active material layers (hereinafter, also referred to as unit layers) formed by compressing a plurality of the granules.

[0040] In one embodiment of the present invention, the electrode active material layer may further contain free electrode active material particles, binder particles, conductive particles, etc., which are derived from granules or are not involved in the formation of granules. In a specific embodiment of the present invention, the electrode active material layer may preferably contain 80 wt% or more, 90 wt% or more, 95 wt% or more, or 99 wt% or more of the granules relative to 100 wt% of the electrode active material layer. In addition, each unit layer may contain 80 wt% or more, 90 wt% or more, 95 wt% or more, or 99 wt% or more of the granules relative to 100 wt% of the unit layer.

[0041] The electrode includes a first unit electrode active material layer to an nth unit electrode active material layer sequentially stacked on a surface of the current collector, where n is an integer of 2 or more, and the nth unit electrode active material layer disposed at the top of the unit electrode active material layers has the highest porosity.

[0042] In the present invention, the electrode active material layer has a multi-layer structure in which n unit layers are sequentially stacked from the surface of the current collector, where n is an integer of 2 or more, and among the n unit layers, a unit layer disposed on the surface of the current collector is referred to as a first unit layer, and a unit layer disposed farthest from the current collector is referred to as an nth unit layer.

[0043] In the present invention, the electrode active material layer has the highest porosity in the uppermost layer (nth unit layer) of each unit layer disposed at the top of the electrode. The uppermost layer refers to the unit layer disposed farthest from the current collector and facing the separator during the manufacture of the electrode.

[0044] The electrode active material layer may have 2 or more, 3 or more, or 5 or more unit layers. The number of the unit layers is not particularly limited, but may be 20 or less, 10 or less, 7 or less, or 5 or less.

[0045] Meanwhile, in one embodiment of the present invention, the thickness of each unit layer in the electrode active material layer may be in the range of 20% to 80% with respect to the thickness of the entire active material layer (100%).

[0046] In the electrode active material layer, the uppermost layer may have a thickness in the range of 20 to 80%.

[0047] In the electrode active material layers, the bottom layer may have a thickness range of 80 to 20%.

[0048] The electrode active material layer has pores provided by interstitial volumes, which are spaces between the granules, and may exhibit porous properties derived from such a structure. In one embodiment of the present invention, the electrode active material layer preferably has a porosity of 20 vol% to 40 vol% in consideration of electrolyte impregnation, dimensional stability, ionic conductivity, and the like.

[0049] Meanwhile, in the present invention, the difference in porosity between each unit layer in surface contact is 1 vol% or more, preferably 2 vol% or more. Meanwhile, the difference in porosity between each unit layer is preferably 20 vol% or less. In a specific example, it may be 10 vol% or less, or 5 vol% or less. In one embodiment of the present invention, it is preferable that the electrode active material layer includes three or more unit layers so that the difference in interlayer porosity is not too steep.

[0050] In one embodiment of the present invention, the porosity of each unit layer may increase in the direction away from the surface of the current collector, with the porosity of the topmost layer being the highest. As the porosity increases toward the topmost layer, lithium ions can be easily transported and a uniform electrochemical reaction can occur in the thickness direction of the electrode active material layer.

[0051] Meanwhile, in a specific embodiment of the present invention, the porosity of the nth unit layer (uppermost layer) may be 50 vol% or less, 40 vol% or less, 35 vol% or less, or 30 vol% or less. In one embodiment, the nth unit layer may have a porosity of 30 vol% to 40 vol%, or 33 vol% to 37 vol%. Also, the first unit layer may have a porosity of 20 vol% or more. If the porosity of the topmost layer is too high or the porosity of the first unit layer is too low, it is difficult to control the porosity of the entire electrode active material layer to an appropriate range, so it is preferable to set the porosity of the topmost layer and the first unit layer to be within the above range.

[0052] In one embodiment of the present invention, the electrode active material layer may include three or more unit layers, and in this case, the difference in porosity between the first unit layer and the uppermost layer is 5 vol% to 20 vol%, preferably 8 vol% to 12 vol%, and more preferably 8 vol% to 12 vol%.

[0053] In one embodiment of the present invention, the binder distribution is uniform in the thickness direction of each unit layer. In a specific embodiment, the difference between the binder content (wt%) in the upper 100 wt% and the binder content (wt%) in the lower 100 wt% may be 10 wt% or less at the upper and lower parts of each unit layer based on 1 / 2 of the height of the unit layer. Such a binder distribution may be due to the fact that the electrode active material layer according to the present invention is manufactured by pressing granules. As described below, the method for manufacturing an electrode of the present invention is characterized in that after manufacturing granule particles containing an electrode material, the granule particles are applied to a current collector and pressed, so that the granules are accumulated in a layered structure. In the case of a method for manufacturing an electrode involving the manufacture of a slurry, the migration of the binder is induced by the evaporation of the solvent when the slurry is dried, and the binder is distributed intensively on the surface of the electrode. However, in the present invention, since a method of compressing and accumulating dry granules without using a solvent is applied, the binder migration phenomenon does not occur, and therefore the binder is uniformly distributed in the thickness direction in each unit layer.

[0054] In the present invention, the granules may have the form of composite particles containing an electrode active material, an electrode binder, and any optional components added as necessary. Specifically, the granules may be secondary particles formed by binding two or more electrode active material particles with the electrode binder and granulating them. In the present invention, the electrode active material may refer to an aggregate of particles. Here, the diameter of each particle of the electrode active material may be 0.05 μm to 2 μm.

[0055] In a specific embodiment of the present invention, the electrode active material may be 80 wt% or more or 90 wt% or more, and the electrode binder may be contained in an amount of 20 wt% or less or 10 wt% or less, based on 100 wt% of the total weight of the granule. In one embodiment of the present invention, the granule may further contain an electrode conductive material as an optional component, if necessary. The electrode conductive material may be contained in a range of 0.1 wt% to 20 wt%, preferably 0.1 wt% to 10 wt%, based on 100 wt% of the granule. For example, the conductive material may be contained in a range of about 0.1 to 5 wt% in the granule.

[0056] According to one embodiment of the present invention, the content of the electrode active material in the granules may be 85wt% to 98wt%. Within this range, the content of the electrode binder may be 0.5wt% to 10wt%, and the content of the electrode conductive material may be 0.5wt% to 5wt%. According to yet another embodiment, the content of the electrode active material may be 90wt% to 98wt%, the content of the electrode binder may be 0.5wt% to 5wt%, and the content of the electrode conductive material may be 0.5wt% to 5wt%.

[0057] Meanwhile, in one embodiment of the present invention, the electrode active material layer may have the same or different electrode materials in each unit layer. For example, each unit layer of the electrode active material layer may contain different electrode active materials, or at least two unit layers in surface contact among the unit layers included in the electrode active material layer may each contain different electrode active materials. In one embodiment of the present invention, when the electrode active material layer is composed of a total of three unit layers, the first unit layer and the second unit layer may each contain different electrode active materials. In addition, or independently, the second unit layer and the third unit layer may each contain different electrode active materials.

[0058] When different types of electrode active materials are used in two opposing unit layers, interference between the electrochemical reactions of the electrode active materials does not occur at the interface between the unit layers, so that the effect of the multi-layer electrode can be further maximized.

[0059] In yet another embodiment, each unit layer includes multiple types of electrode active materials, and the combination of components (types) of the multiple electrode active materials in each unit layer is the same, but the content ratio between the components in each unit layer may be different.

[0060] More preferably, the granules in each unit layer contain a plurality of types of electrode active materials, and the granules in each unit layer have the same combination of the components (types) of the plurality of electrode active materials, but the content ratio of each component in the granules in each unit layer may be different.

[0061] In a specific embodiment, when the electrode is a negative electrode, the electrode active material layer may include artificial graphite and / or natural graphite as a negative electrode active material. In one embodiment of the present invention, the content of artificial graphite and natural graphite in the granules may differ from unit layer to unit layer. Specifically, the content of artificial graphite in the granules may increase from the first unit layer to the nth unit layer. Independently or in addition, the amount of natural graphite in the granules may decrease from the first unit layer to the nth unit layer, which is the top layer. In this way, the content of artificial graphite in the granules increases and the content of natural graphite decreases toward the top layer, and simultaneously or independently, the content of artificial graphite in the granules decreases and the content of natural graphite increases toward the bottom layer. Even if each layer is pressed with the same or similar pressure, the porosity of each unit layer differs due to the inherent pressing difference of each granule, and in particular, an electrode active material layer having the highest porosity in the top layer can be obtained.

[0062] In a specific embodiment of the present invention, a first unit layer, which is the lowest layer of the electrode active material layer, includes a plurality of first granules, and the first granules include an electrode active material that includes natural graphite and artificial graphite, and the content of natural graphite in the first granules may be 50 wt% or more, or 70 wt% or more, relative to 100 wt% of the electrode active material. Preferably, the content of the first granules in the first unit layer may be 90 wt% or more, more preferably 99 wt% or more, relative to 100 wt% of the unit layer.

[0063] In addition, in a specific embodiment of the present invention, the nth unit layer, which is the uppermost layer of the electrode active material layer, includes a plurality of nth granules, and the nth granules may include only artificial graphite as an electrode active material, or may include natural graphite and artificial graphite, and the nth granules may include 80 wt% or more of artificial graphite, preferably 90 wt% or more or 99 wt% or more of artificial graphite, relative to 100 wt% of the electrode active material. Preferably, the nth unit layer may include 90 wt% or more of nth granules, preferably 99 wt% or more of nth granules, relative to 100 wt% of the unit layer.

[0064] In the second layer, third layer, ..., n-2 layer, n-1 layer disposed between the first layer and the nth layer, the content of artificial graphite in the granules may increase toward the nth layer, and the content of natural graphite in the granules may increase toward the first layer.

[0065] In a specific embodiment of the present invention, the electrode active material layer may have a configuration in which a first unit layer, a second unit layer, and a third unit layer are stacked in order.

[0066] In a specific embodiment of the present invention, a first unit layer, which is the lowest layer of the electrode active material layer, includes a plurality of first granules, the first granules are made of an electrode active material consisting of natural graphite and artificial graphite, and the content of natural graphite (Nc1) in the first granules may be 50 wt% or more, or 70 wt% or more, relative to 100 wt% of the electrode active material. Preferably, the content of the first granules in the first unit layer may be 90 wt% or more, more preferably 99 wt% or more, relative to 100 wt% of the unit layer.

[0067] In addition, the second unit layer includes a plurality of second granules, and the second granules include an electrode active material made of natural graphite and artificial graphite, and the content of natural graphite (Nc2) in the second granules may be adjusted to a range of 30wt% to 70wt%, preferably 30wt% to 50wt%, based on 100wt% of the electrode active material, and is smaller than Nc1. Preferably, the second unit layer includes the content of the second granules in the second unit layer of 90wt% or more, more preferably 99wt% or more, based on 100wt% of the unit layer.

[0068] And the third unit layer includes a plurality of third granules. The third granule contains only artificial graphite as the electrode active material or consists of natural graphite and artificial graphite. In the third granule, the content of artificial graphite (Ac3) may exceed 70 wt%, be 80 wt% or more, desirably 90 wt% or more, or 99 wt% or more with respect to 100 wt% of the electrode active material. Desirably, the content of the third granule may be 90 wt% or more, desirably 99 wt% or more in 100 wt% of the unit layer. Also, the content of artificial graphite (Ac1) with respect to 100 wt% of the electrode active material in the first granule, the content of artificial graphite (Ac2) with respect to 100 wt% of the electrode active material in the second granule, and the content of artificial graphite (Ac3) with respect to 100 wt% of the electrode active material in the third granule are desirably such that Ac1 < Ac2 < Ac3.

[0069] FIG. 1 is according to an embodiment of the present invention and schematically shows a cross-section of an electrode including three unit layers. In the electrode 100, an electrode active material layer 110 is disposed on the surface of a current collector 120, and the electrode active material layer has a first unit layer 111, a second unit layer 112, and a third unit layer 113 sequentially laminated from the surface of the current collector. Here, the electrode active material layer has a porosity in the range of 20 vol% to 40 vol%. The porosity of the first unit layer is 20 vol% or more, the porosity of the third unit layer is 40 vol%, and the difference between the porosity of the first unit layer and the porosity of the third unit layer may be 5 vol% to 15 vol%. On the other hand, the difference in porosity between the first and second unit layers and the difference in porosity between the second and third unit layers may each independently be 1 vol% or more.

[0070] Also, in each of the first to third unit layers, based on half of the height of the unit electrode active material layer, the difference between the content (wt%) of the binder in the upper part at 100 wt% and the content (wt%) of the binder in the lower part at 100 wt% may be 10 wt% or less.

[0071] In the present invention, the amount of electrode binder contained in the surface portion 102 of the granule may be greater than the amount of electrode binder contained in the center portion 101 of the granule 100. The amount of binder may refer to weight or volume. Figure 3 is a schematic diagram showing the surface portion and center portion of a granule 100 according to one embodiment of the present invention.

[0072] In addition, or independently, the granule has a content (wt%) B of the electrode binder contained in the center of the granule relative to the total weight of the granule (100 wt%). c / G t The content (wt%) of the electrode binder contained in the surface area of ​​the granules is B s / G t Here, the B c is the weight of the binder contained in the core, and B s is the weight of the binder contained in the surface area, and G t means the total weight of the granule particles.

[0073] In addition, or independently, the granule has a content (vol%) B of the electrode binder contained in the center of the granule relative to 100 vol% of the total volume of the granule. c / G t The content of the electrode binder in the surface area of ​​the granule is vol%B s / G t Here, the B c is the volume of the binder contained in the core, and B s is the volume of the binder contained in the surface area, and G t means the total volume of the granule particles.

[0074] Here, the surface portion may be a region near the surface of the granule from the surface of the granule to a predetermined depth toward the center of the granule. The central portion means a portion other than the surface portion. In one embodiment of the present invention, the surface portion may mean, more specifically, a surface region from the surface of the granule toward the inside, specifically, up to 30% of the radius toward the center of the granule. In one embodiment of the present invention, the surface portion may mean a surface region from the surface of the granule to 30% of the radius, up to 20% of the radius, up to 15% of the radius, up to 10% of the radius, or up to 5% of the radius. Desirably, the surface portion may mean a surface region from the surface of the granule to 20% of the radius.

[0075] Meanwhile, in one embodiment of the present invention, the surface portion may refer to a region from the center of the granule to the outside of the granule, which is 70% or more of the radius of the granule surface. In one embodiment of the present invention, the surface portion may refer to a region from the center of the granule to the outside of the granule, which is 80% or more, 85% or more, 90% or more, or 95% or more of the radius of the granule surface.

[0076] In one embodiment of the present invention, the center of the granule may refer to a point that is 1 / 2 the maximum diameter of the granule. In the present invention, the radius may refer to a distance from the center of the granule to each point on the granule surface. In one embodiment of the present invention, the surface portion and the center portion may be divided based on a point that is the same distance from each surface of the granule along each radius, specifically, a point up to 30%, 20%, 10%, 5%, or 1% of the radius from the surface.

[0077] In one embodiment of the present invention, in a region from the center of the granule to the surface of the granule at a radius of 90% or more, the content of the electrode binder relative to the total weight of the granule in that region (100 wt%) may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0078] In yet another embodiment of the present invention, in a region from the center of the granule to a radius of 95% or more of the granule surface, the content of the electrode binder relative to 100 wt% of the total weight of the granule in that region may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0079] In yet another embodiment of the present invention, in a region from the center of the granule to a radius of 99% or more of the granule surface, the content of the electrode binder relative to 100 wt% of the total weight of the granule in that region may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0080] In one embodiment of the present invention, in a region from the center of the granule to a radius of 90% or more of the granule surface, the content of the electrode binder relative to 100 vol% of the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0081] In yet another embodiment of the present invention, in a region from the center of the granule to a radius of 95% or more of the granule surface, the content of the electrode binder relative to 100 vol% of the total volume of the granule in the region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0082] In yet another embodiment of the present invention, in a region from the center of the granule to a radius of 99% or more of the granule surface, the content of the electrode binder relative to 100 vol% of the total volume of the granule in the region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0083] To describe the granule in more detail, the granule may have a center portion including a plurality of electrode active materials, and a surface portion including an electrode binder located on all or a part of the outside of the center portion and binding the electrode active materials. That is, in the center portion of the granule, the plurality of electrode active materials are in surface contact, line contact, point contact, or contact with two or more of these to form an aggregate, and in the surface portion of the granule, an electrode binder is located on all or a part of the outside of such an aggregate to fix and bind the plurality of electrode active materials in the center portion of the granule.

[0084] According to an embodiment of the present invention, the center portion may further include a small amount of electrode binder to connect and fix the plurality of electrode active materials in the center portion to each other. However, as described above, it is preferable that the content of the electrode binder is higher in the surface portion than in the center portion.

[0085] Meanwhile, in one embodiment of the present invention, the granule may have an aspect ratio of 0.5 to 1.0, preferably 0.75 to 1.0. The aspect ratio may mean the ratio of the length of the short axis of the granule to the length of the long axis. In yet another embodiment of the present invention, the average aspect ratio of the granule may have a value of 0.5 to 1.0, preferably 0.75 to 1.0, in which case the average aspect ratio may mean the ratio of the average length of shortening of the granule particles to the average length of the long axis. In this case, the average length of shortening may mean the average length of the granule in the axial direction having the shortest length, and the average length of the long axis may mean the average length of the granule in the axial direction having the longest length. When the aspect ratio of the granule satisfies such a range, it is advantageous in terms of having sufficient fluidity suitable for processing.

[0086] Meanwhile, in one embodiment of the present invention, the granules may have a particle size in the range of 0.1 to 1,000 μm based on the longest diameter of the particle. In yet another embodiment of the present invention, the granules may have an average particle size D50 in the range of 0.1 to 1,000 μm.

[0087] In one embodiment of the present invention, when the electrode is a negative electrode, the electrode active material is, as a negative electrode active material, for example, a carbon material such as graphitizable carbon and / or non-graphitizable carbon; graphite-based carbon such as natural graphite and / or artificial graphite; Li x Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon; silicon-based alloy; tin; tin-based alloy; silicon-based oxides such as SiO, SiO / C, SiO2; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials, etc. can be used. However, it is not limited to these only.

[0088] On the other hand, in one embodiment of the present invention, when the electrode is a positive electrode, the electrode active material is, as a positive electrode active material, a layered compound such as lithium manganese composite oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; chemical formula Li 1+x Mn 2-x O4 (where x is 0 to 0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7; chemical formula LiNi 1-x M x O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3), Ni-site type lithium nickel oxide represented by; chemical formula LiMn 2-x M xLithium manganese composite oxides represented by Li2Mn3MO8 (where M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1) or Li2Mn3MO8 (where M=Fe, Co, Ni, Cu or Zn); Li in which part of the Li in the chemical formula is replaced by an aluminum ion. 1+x (Ni a Co b MncAl d ) 1-x O2 (x=0-0.03, a=0.3-0.95, b=0.01-0.35, c=0.01-0.5, d=0.001-0.03, a+b+c+d=1); disulfide compounds; and Fe2(MoO4)3, or a mixture of two or more of them.

[0089] The electrode binder is not limited to a specific component as long as it has adhesiveness and is stable in an electrochemical reaction, can bind the electrode active material and the electrode material such as the electrode conductive material to maintain a granular form, and can accumulate in a layered structure by binding the granules to each other through compression to maintain a stable form.Non-limiting examples of such electrode binders include styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), styrene butadiene styrene block polymer (SBS), styrene ethylene butadiene block polymer (SEB), styrene-(styrene butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), ethylene-propylene diene terpolymer (EPDM), poly(ethylene-co-propylene-co-5-methylene-2-norbornene), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), polyvinyl chloride, polyvinylidene fluoride-hexafluoropropylene (PVDF), ... The polymerizable compound may include polyvinyl fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene, polypropylene, ethylene-vinyl acetate, polyethylene oxide, polypropylene oxide, polyarylate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, or two or more thereof.Specifically, the binder may be styrene butadiene rubber (SBR), nitrile butadiene rubber (NBR), polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, etc. In a specific embodiment, the electrode binder may include one or more selected from the above.

[0090] The electrode conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. Non-limiting examples include graphite such as natural graphite and artificial graphite; carbon black-based carbon compounds such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. In a specific embodiment, the electrode conductive material may include one or more selected from these.

[0091] The current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. The current collector may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The current collector may also be formed with fine irregularities on its surface to increase the adhesive strength of the active material, and may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. Meanwhile, in one embodiment of the present invention, the current collector may have a thickness of 10 μm to 50 μm, but is not particularly limited thereto. The current collector may have a thickness of, for example, 10 μm to 20 μm.

[0092] Meanwhile, in the present invention, the current collector may have a primer layer formed on at least one surface thereof, covering all or at least a portion of the surface. The primer layer may be introduced to improve the binding strength between the current collector and the electrode active material layer and electrical conductivity. The primer layer may include a second conductive material and a second binder resin. The second conductive material may be as described above for the electrode conductive material. The second binder resin may be as described above for the electrode binder.

[0093] Meanwhile, in yet another embodiment of the present invention, the primer layer may have the following structural features.

[0094] The primer layer includes a binder for the primer layer (hereinafter, the second binder) and a conductive material for the primer layer (hereinafter, the second conductive material), and the sum of the contents of the second binder and the second conductive material in the primer layer may be 90 wt% or more.

[0095] An electrode according to an embodiment of the present invention includes an electrode active material layer including granules, and in this case, a primer layer including a second binder and a second conductive material, the sum of the contents of the second binder and the second conductive material being 90 wt% or more, ensures stability over time of the primer layer, and thus exhibits excellent physical properties such as adhesive strength and life characteristics, but the present invention is not limited thereto.

[0096] According to an embodiment of the present invention, the primer layer includes a second binder and a second conductive material, and may further include a dispersant.

[0097] According to another embodiment of the present invention, the primer layer may include a second binder and a second conductive material, but may be substantially free of a dispersant.

[0098] According to an embodiment of the present invention, the second binder may be any binder known to be used in a primer layer without any particular limitation.

[0099] According to another embodiment of the present invention, the second binder may be a polymer capable of ensuring stability over time of the primer layer, and more specifically, the second binder may have a glass transition temperature (Tg) of 45° C. or less.

[0100] According to another embodiment of the present invention, the second binder may be, for example, styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), styrene butadiene styrene block polymer (SBS), styrene ethylene butadiene block polymer (SEB), styrene-(styrene butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), ethylene-propylene-diene terpolymer (EPDM), poly(ethylene-co-propylene-co-5-methylene-2-norbornene), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), polyvinyl chloride, polyvinylidene fluoride-hexafluoropropylene (PVDF), ... The polymer may include polyvinyl fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene, polypropylene, ethylene-vinyl acetate, polyethylene oxide, polypropylene oxide, polyarylate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, or two or more thereof.Specifically, the binder may include styrene butadiene rubber (SBR), nitrile butadiene rubber (NBR), polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, or two or more thereof.

[0101] According to yet another embodiment of the present invention, the second binder has the above-mentioned glass transition temperature value and may be one or a mixture of two or more selected from the above-mentioned types.

[0102] According to yet another embodiment of the present invention, the second binder may be a styrene butadiene rubber (SBR) having a glass transition temperature Tg of -40°C to 45°C, a nitrile butadiene rubber (NBR) having a glass transition temperature Tg of -40°C to 45°C, or a mixture thereof.

[0103] According to one embodiment of the present invention, the specific surface area of ​​the second conductive material is 30 m 2 / g~1,400m 2 / g and may be spherical. In this case, the size of the primary particles of the spherical conductive material may be, for example, 10 nm to 100 nm, specifically 15 nm to 70 nm, but is not limited thereto.

[0104] According to another embodiment of the present invention, the second conductive material has a specific surface area of ​​10 m 2 / g~400m 2 In this case, the diameter of the cross section of the tubular conductive material in the direction perpendicular to the longitudinal direction may be 0.1 to 3 nm, specifically 0.3 to 1.5 nm, but is not limited thereto.

[0105] The second conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black-based carbon compounds such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used. In particular, in order to uniformly mix the conductive material and improve conductivity, the second conductive material may include activated carbon, graphite, carbon black, carbon nanotubes, or a mixture of two or more of these, and more particularly, may include activated carbon.

[0106] According to an embodiment of the present invention, the primer layer may have the above-mentioned composition and a thickness of 300 nm to 1.5 μm, specifically, 700 nm to 1.3 μm, but is not limited thereto.

[0107] A method for producing an electrode according to the present invention will now be described.

[0108] First, granules containing an electrode material are prepared. The granules may be prepared by mixing an electrode active material and an electrode binder with a solvent to prepare a fluidized slurry, and then spray-drying the slurry. In one embodiment of the present invention, the granules may further include an electrode conductive material as necessary. In addition, other additives for improving performance may be further included.

[0109] First, the electrode active material, the electrode binder, and optionally an additional additive are dispersed or dissolved in a dispersion medium (solvent for the electrode binder) to obtain a slurry in which the electrode active material and the electrode binder are dispersed or dissolved.

[0110] The dispersion medium used to obtain the slurry is most preferably water, but an organic solvent may be used. Examples of organic solvents include alkyl alcohols such as methyl alcohol, ethyl alcohol, and propyl alcohol; alkyl ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran, dioxane, and diglyme; amides such as diethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone (hereinafter also referred to as NMP), and dimethylimidazolidinone; sulfur-based solvents such as dimethyl sulfoxide and sulfolane; and the like, with alcohols being preferred. The combined use of an organic solvent with a boiling point lower than that of water can increase the drying speed during fluidized granulation. In addition, the dispersibility or solubility of the negative electrode binder can change, so that the viscosity and fluidity of the slurry can be adjusted according to the amount or type of the dispersion medium, thereby improving production efficiency.

[0111] The amount of the dispersion medium used when preparing the slurry may be an amount such that the solids concentration of the slurry is usually in the range of 1 to 50 wt%, or 5 to 50 wt%, or 10 to 30 wt%.

[0112] The method or order of dispersing or dissolving the electrode active material and electrode binder in the dispersion medium is not particularly limited, and examples thereof include a method of adding the electrode active material and electrode binder to the dispersion medium and mixing them, and a method of dissolving or dispersing the electrode binder in the dispersion medium and then adding the electrode active material and mixing them. When a conductive material or additive is included, these components may be added when the electrode active material is added. Examples of mixing means include mixing devices such as a ball mill, a sand mill, a bead mill, a pigment disperser, a stone mill, an ultrasonic disperser, a homogenizer, and a planetary mixer. Mixing may be performed, for example, at room temperature to 80° C. for 10 minutes to several hours.

[0113] Next, the slurry is spray-dried. The spray drying method is a method of spraying the slurry into hot air and drying it. Examples of the spraying method of the device used in the spray drying method include a rotating disk method and a nozzle pressurization method. The rotating disk method is a method in which the slurry is introduced into the approximate center of a disk rotating at high speed, and when the slurry is removed from the disk by the centrifugal force of the disk, it is sprayed in a mist form and dried. The rotation speed of the disk depends on the size of the disk, but is usually 5,000 to 35,000 rpm, preferably 15,000 to 30,000 rpm. On the other hand, the pressurization method is a method in which the slurry is pressurized and sprayed in a mist form from a nozzle to dry it.

[0114] Meanwhile, the temperature of the slurry to be sprayed may be room temperature, but it is preferable to heat it to room temperature or higher in order to form a granular structure with a high content of electrode binder on the surface. In one embodiment of the present invention, the hot air temperature (based on the temperature at the reactor inlet) during spray drying is usually 80°C to 250°C, preferably 100°C to 220°C. More preferably, it is 180°C to 220°C. In the spray drying method, the method of inhaling the hot air is not particularly limited, and examples thereof include a method in which the hot air and the spray direction flow sideways in parallel, a method in which the sprayed liquid droplets are sprayed from the top of the drying tower and fall together with the hot air, a method in which the sprayed liquid droplets flow sideways in parallel with the initial hot air, and then fall by gravity to come into countercurrent contact. Meanwhile, in one embodiment of the present invention, the outlet temperature of the reactor (the hot air temperature discharged from the reactor) during the spray drying may be controlled to 90°C to 130°C.

[0115] Optionally, the product obtained by spray drying, i.e., the granules, may be heat-treated to harden the surface thereof. In this case, the heat-treatment temperature may be generally 80°C to 300°C.

[0116] Next, the granules are spread on the surface of the electrode current collector and pressed to form a first unit layer having a layered structure with a predetermined thickness. After that, when the first unit layer is formed, additional granules are applied and pressed on the top of the first unit layer to form a unit layer, and the application and pressing process is repeated until an electrode active material layer having a predetermined number of unit layers is obtained. The pressure applied during the formation of each unit layer may be controlled so that each unit layer has an appropriate porosity, as described above. Meanwhile, in one embodiment of the present invention, granules having different components or electrode active material contents (and / or content ratios) may be prepared for each unit layer, and the granules may be selected and introduced according to the characteristics of each unit layer. Each unit layer may be formed as follows.

[0117] At least one surface of the current collector may be provided with a primer layer including a second conductive material and a second binder as described above.

[0118] According to an embodiment of the present invention, a plurality of prepared granules may be supplied to a roll-type pressure molding device using a supply device such as a screw feeder to form unit layers. When forming the first unit layer, the current collector may be fed to the roll of the pressure molding device at the same time as the granules are supplied, so that the first unit layer may be directly laminated on the current collector. Alternatively, the granules may be spread on the current collector, the granules may be uniformly cut with a blade or the like to adjust the thickness, and then molded with a pressure device to form the first unit layer. In the process after the formation of the first unit layer, each unit layer is formed by a method in which the granules are spread on the surface of the lower unit layer instead of the current collector, the granules may be uniformly cut with a blade or the like to adjust the thickness, and then molded with a pressure device.

[0119] In these methods, the temperature during roll pressure molding is usually 0°C to 200°C, which is desirably higher than the melting point or glass transition temperature of the negative electrode binder, and more desirably 20°C or more higher than the melting point or glass transition temperature. The molding speed in roll pressure molding can usually be 0.1 to 20 m / min, or 1 to 10 m / min. The linear pressure of the press between the rolls can usually be 0.2 to 30 kN / cm, or 0.5 to 10 kN / cm.

[0120] In order to eliminate thickness variations in each molded unit layer and increase the density of the unit layer and the electrode active material layer to increase capacity, pressurization may be further performed as necessary. The post-press method is generally a press process using a roll. In the roll press process, two cylindrical rolls are set up parallel to each other with a narrow gap between them and rotated in opposite directions to sandwich the electrode between them and apply pressure. The temperature of the rolls may be adjustable by heating or cooling.

[0121] The present invention has been described above with reference to the embodiments and drawings. However, a person having ordinary knowledge in the field to which the present invention belongs will be able to make various applications and modifications within the scope of the present invention based on the above content.

[0122] Example 1 (1) Preparation of current collector with primer layer Carbon black (specific surface area: 30 m 2 / g, particle size: 70 nm), 30 parts by weight, styrene butadiene rubber (SBR) (T g The slurry for the primer layer was prepared by mixing 69 parts by weight of ethylenediaminetetraacetate (ethylenediaminetetraacetate) (at -15°C) and 1 part by weight of carboxymethylcellulose (CMC) as a dispersant with water as a dispersion medium. The content ratio of the conductive material, binder, and dispersant in the slurry was the same as the content ratio of the conductive material, binder, and dispersant in the primer layer to be formed later. The solid content of the slurry for the primer layer was 7 wt%.

[0123] The prepared primer layer slurry was applied to one surface of a copper current collector (thickness: 10 μm) and dried at 130° C. to form a primer layer on the surface of the copper current collector.

[0124] (2) Preparation of granules for negative electrode active material layer First granules, second granules and third granules were prepared, and the content ratio of natural graphite and artificial graphite in each granule was as shown in Table 1 below.

[0125] [Table 1]

[0126] Each granule was manufactured in the following manner. The negative electrode active material, carbon black (SuperC65), carboxymethylcellulose (daicel2200, aqueous solution, solid content concentration 1.5wt%), and modified styrene butadiene copolymer (Grade Name AX-B119) were mixed with water as a dispersion medium in a weight ratio of 95.6:1.0:1.1:2.3 to manufacture a slurry with a viscosity of about 1,000cPs using a homogenizer. At this time, the solid content of the slurry was 30wt%. In the above weight ratio, the carboxymethylcellulose was calculated based on the solid content. The manufactured slurry was dried by feeding it into a spray dryer together with hot air under a pressure range of -40mmH2O. At this time, the conditions of the spray dryer were controlled to an inlet temperature of about 180°C, an outlet temperature of about 90°C, and a rotation speed of about 18,000rpm. The obtained granules were sieved through an industrial sieve to remove coarse particles of 150 μm or more, and fine particles of less than 40 μm were further separated. The separated fine particles were mixed with the granules from which only the coarse particles were removed to finally prepare anode granules containing more fine particles than the previous granules. The average particle size D50 of each granule obtained was about 66.5 μm, and the aspect ratio was about 0.96. Figure 4 shows an SEM image of the first granules obtained by the above preparation, and the bright areas indicated by the arrows indicate the binder resin. The obtained first granules were dyed with OsO4 to dye the binder in each granule. The first granules were placed in each glass container using OsO4 crystals or an aqueous solution, and then the reagent was evaporated to react. The mixture was then mixed with epoxy resin, fixed in a silicon mold, and hardened to obtain a granule matrix. Next, a cross-sectional sample was prepared from the granular matrix using an ion milling device (Hitachi IM5000, accelerating voltage: 6 kV), and then an SEM image was obtained.

[0127] (3) Manufacturing of negative electrodes The first granules were applied to one surface of the current collector having the primer layer by using a thickness adjusting bar. 2 The first layer was formed by roll-to-roll hot rolling. The second layer was then applied to the surface of the first layer at a thickness of 25 cm. 2 The third granule was then applied uniformly to the surface of the second layer at a thickness of 25 cm. 2 The coating was uniformly applied in an amount of 120 mg per cm and hot rolled by roll-to-roll to form the third layer. When forming the first, second and third layers, each roll was performed at about 60°C, with a pressure of 0.7 ton per cm and a speed of 2 m per minute.

[0128] Comparative Example 1 As negative electrode active materials, natural graphite with an average sphericity of 0.95 and artificial graphite with an average sphericity of 0.9 were prepared.

[0129] Next, slurries for forming the first, second and third layers were prepared. Each slurry was prepared by mixing a negative electrode active material, carbon black (Super-C 65), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC) and water, and the solid content in the slurry was about 47 wt%. The negative electrode active material, carbon black, SBR and CMC were mixed in a ratio of about 95.6:1.0:2.3:1.1 based on a weight ratio. The content ratio of artificial graphite and natural graphite in each layer was prepared as shown in Table 2 below.

[0130] [Table 2]

[0131] Next, the first layer forming slurry, the second layer forming slurry, and the third layer forming slurry were sequentially applied to the current collector prepared in Example 1 using a slot die. Then, the first layer forming slurry, the second layer forming slurry, and the third layer forming slurry were dried using a drying device equipped with a hot air blower and an IR (infrared) heater, and rolled by a roll pressing method to manufacture a negative electrode having a negative electrode active material layer. The loading amount of the negative electrode active material layer per unit area was 360 mg / 25 cm. 2 The electrode active material layer was rolled at about 60° C. under a pressure of 0.7 ton per cm at a speed of 2 m per minute.

[0132] Comparative Example 2 A slurry for forming the first layer, a slurry for forming the second layer, and a slurry for forming the third layer were prepared in the same manner as in Comparative Example 1. Next, the slurry for forming the first layer was applied to the current collector prepared in Example 1 using a slot die and dried to form a first layer. Next, the slurry for forming the second layer was applied to the top of the first layer and dried to form a second layer. Then, the slurry for forming the third layer was applied to the top of the second layer and dried. The drying was performed using a drying device equipped with a hot air blower and an IR (infrared) heater. Then, the mixture was rolled using a roll press method to manufacture a negative electrode having a negative electrode active material layer. The loading amount of the negative electrode active material layer was 360 mg / 25 cm per unit area. 2 The electrode active material layer was rolled at about 60° C. under a pressure of 0.7 ton per cm at a speed of 2 m per minute.

[0133] Comparative Example 3 A single-layer electrode was manufactured using the first granules prepared in Example 1. The first granules were attached to one side of the current collector prepared in Example 1 by using a thickness adjusting bar to a thickness of 25 cm. 2 The electrode active material layer was formed by hot rolling at a pressure of 0.7 ton per cm at about 60° C. and a speed of 2 m per min.

[0134] Comparative Example 4 An electrode was manufactured using the first, second, and third granules prepared in Example 1. The electrode was manufactured in the same manner as in Example 1, except that the third granules were applied to the surface of the current collector to form a first layer, then the second granules were used to form a second layer, and the first granules were applied to the surface of the second layer to form a top layer.

[0135] Porosity measurement The porosity of the electrode active material layer was measured for each of Example 1, Example 2, and Comparative Examples 1 to 4. For the single-layer electrode, the porosity of the entire electrode active material layer was measured, and for the multilayer electrode, the overall porosity of the entire electrode active material layer was measured, and the porosity was measured for each layer.

[0136] The thickness of the entire electrode active material layer and the thickness of each unit layer were obtained from a SEM image of the cross section of the electrode active material layer. The porosity can be calculated by calculating the electrode active material layer from the composition ratio of the materials contained in the electrode active material layer and the density of each component, and then calculating from the difference between the apparent density and the net density. Specifically, the porosity can be calculated according to the following Equation 1.

[0137] [Formula 1] Porosity (vol%) = {1-(apparent density / true density)} x 100

[0138] On the other hand, in the above formula, the apparent density can be calculated from the following formula 2.

[0139] [Formula 2] Apparent density (g / cm 3 ) = {Weight of electrode active material layer [g] / (Thickness of electrode active material layer [cm] × Area of ​​electrode active material layer [cm 2 ])}

[0140] The porosity calculated from each of the examples and comparative examples is as shown in Table 3 below.

[0141] [Table 3]

[0142] Battery manufacturing Batteries were manufactured using the negative electrodes obtained in Example 1 and Comparative Examples 1 to 4. 0.8 Co 0.1 Mn 0.1 O2, PVdF and carbon black were mixed in a weight ratio of 97.0:1.5:1.5, and dispersed in 2-methyl-2-pyrrolidone to prepare a cathode slurry, which was then coated on an aluminum current collector, dried and rolled to prepare a cathode. A porous film made of polyethylene material was interposed between the anode and cathode to prepare a battery. The electrolyte used was a mixture of ethylene carbonate:ethyl methyl carbonate in a volume ratio of 1:2, to which LiPF6 was added at a concentration of 1M.

[0143] Capacity retention rate evaluation Each battery of Example 1 and Comparative Examples 1 to 4 was charged at 0.33 C until the voltage reached 0.01 V (Vs. Li), and then discharged at the same current until the voltage reached 3 V. Then, charging and discharging were repeated 200 times at the same current and voltage range. The charging and discharging were performed at an ambient temperature of about 45° C.

[0144] The capacity retention rate can be calculated by the following formula 3.

[0145] [Formula 3] Capacity maintenance rate (%)=[200 th Discharge capacity of cycle / 2 nd Discharge capacity of cycle x 100

[0146] [Table 4]

[0147] It was confirmed that the battery of Example 1 had an excellent capacity retention rate. On the other hand, the battery of Comparative Example 2 had a high porosity in the upper layer, but showed a very low capacity retention rate. This is because the upper layer was rapidly deteriorated due to resistance generated at the interlayer interface, which resulted in a decrease in the capacity retention rate. On the other hand, it was confirmed that when the porosity of the electrode surface was low, as in Comparative Examples 3 and 4, the capacity retention rate decreased.

[0148] EIS characterization Resistance was measured from electrochemical impedance spectroscopy analysis results using Solaton's 1470E cell test system and Frequency response analyzer 1255B under conditions of 25°C, amplitude 10mV, and scan range 2000Hz~0.1Hz, and the Nyquist plot is shown in FIG. 2. Referring to this, it was confirmed that the battery of Example 1 did not generate additional resistance. Meanwhile, it was confirmed that the batteries of Comparative Example 2 and Comparative Example 4 generated additional resistance. In Comparative Example 2, the porosity of the electrode surface was high, but the binder component of the upper slurry flowed into the pores of the lower unit layer when the slurry was applied to the upper part of each dried unit layer, and the pores were blocked, resulting in a decrease in the interface resistance characteristics. Meanwhile, in Comparative Example 4, the electrolyte did not easily flow into the electrode, resulting in a decrease in the resistance characteristics.

Claims

1. An electrode for an electrochemical element comprising a current collector and an electrode active material layer disposed on at least one surface of the current collector, the electrode active material layer includes a unit electrode active material layer in which a plurality of granules including an electrode active material and an electrode binder are accumulated, and a first unit electrode active material layer to an n-th unit electrode active material layer are sequentially stacked on a surface of the current collector, where n is an integer of 2 or more; An electrode for an electrochemical device, wherein an uppermost unit electrode active material layer of an n-th unit electrode active material layer included in the electrode active material layer has the highest porosity.

2. 2. The electrode for an electrochemical element according to claim 1, wherein said n is 3 or more and 10 or less.

3. 2 . The electrode for an electrochemical device according to claim 1 , wherein the nth unit electrode active material layer, which is the uppermost layer among the electrode active material layers, has a porosity of 40 vol % or less.

4. 2 . The electrode for an electrochemical device according to claim 1 , wherein the first unit electrode active material layer has a porosity of 20 vol % or more.

5. The electrode for an electrochemical device according to claim 1 , wherein the porosity of each unit electrode active material layer increases with increasing distance from the surface of the current collector.

6. 2. The electrode for an electrochemical element according to claim 1, wherein each unit electrode active material layer contains a plurality of types of electrode active materials, and the combination of the components of the plurality of electrode active materials is the same in each unit electrode active material layer, but the content ratio between the components is different in each unit electrode active material layer.

7. 7. The electrode for an electrochemical element according to claim 6, wherein the granules contained in each unit electrode active material layer contain a plurality of types of electrode active materials, and the combination of the components of the plurality of electrode active materials is the same in the granules of each unit electrode active material layer, but the content ratio of the components of each granule in each unit electrode active material layer is different.

8. 2. The electrode for an electrochemical element according to claim 1, wherein a difference between a binder content (wt%) in the upper 100 wt% and a binder content (wt%) in the lower 100 wt% is 10 wt% or less at an upper and lower part of each unit electrode active material layer, based on ½ of the height of the unit electrode active material layer.

9. 2. The electrode for electrochemical elements according to claim 1, wherein n is 3 or more, and a difference in porosity between the lowermost first unit electrode active material layer and the uppermost nth unit electrode active material layer is 5 vol% to 20 vol%.

10. 2. The electrode for an electrochemical element according to claim 1, wherein the electrode is a negative electrode, and the electrode active material comprises at least one selected from the group consisting of natural graphite, artificial graphite, and lithium (Li), silicon (Si), tin (Sn), a lithium alloy, a silicon alloy, a tin alloy, a silicon oxide, a tin oxide, a lithium-containing compound, a silicon-containing compound, and a tin-containing compound.

11. The electrode for an electrochemical element according to claim 1 , wherein the granules contain an electrode conductive material.

12. 2. The electrode for an electrochemical element according to claim 1, wherein the current collector has at least one surface formed with a primer layer that covers all or at least a part of the surface, the primer layer including a conductive material and a binder.

13. 11. A method for manufacturing an electrode for an electrochemical device, comprising: forming a first unit electrode active material layer having a layered structure with a predetermined thickness by applying an electrode powder to one surface of a current collector and pressing the surface; and then, forming a unit electrode active material layer by applying an additional electrode powder to a surface of each unit electrode active material layer formed in the previous step and pressing the surface, the step being repeated n-1 times to manufacture an electrode including n unit electrode active material layers, the electrode having the structure of the electrode for an electrochemical device according to claim 1, wherein n is an integer of 2 or more.

Citation Information

Patent Citations

  • Secondary battery electrode

    JP2015011902A

  • Method of manufacturing electrode for lithium ion secondary battery

    JP2015230748A

  • Method of manufacturing nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2016134237A

  • Multi-Layered Electrode of Different Porosity and Method for Preparation of the Same

    KR1020160118586A